1995
DOI: 10.1016/0736-5748(95)00079-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic and acute oestrogen treatment on the developing noradrenaline‐containing nerves of the rat uterus

Abstract: The developing noradrenaline-containing (NA-C) sympathetic nerves of the rat uterus were analyzed following acute and chronic treatment with oestrogen. Histochemical methods were used in association with nerve density measurements and biochemical assays. For comparative purposes, noradrenaline (NA) levels were measured in the urinary bladder and right auricle following chronic oestrogen treatment. Acute treatment was performed by s.c. administration of a single dose of 40 micrograms oestradiol cypionate on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…Considering that the reduced intercept density of these nerve fibers did not persist after correction for changes in the target, it might be suggested that estrogen provoked the "dilution" of those cholinergic fibers by its hypertrophic effects on the myometrium. Dilution of the sympathetic myometrial nerve fibers that fail to keep pace with the size of the uterus was also seen in the rat during puberty (Brauer et al 1992) and after acute (Brauer et al 1995) and chronic exposure to estrogen of young adult rats (Chávez-Genaro et al, In press). This unusual behavior of uterine sympathetic nerves clearly contrasts with the responses of similar nerves in other hypertrophic target tissues, including muscular visceral organs, in which changes in target size induce coordinated changes in their innervating neurons (Gabella 1984;Steers et al 1990).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering that the reduced intercept density of these nerve fibers did not persist after correction for changes in the target, it might be suggested that estrogen provoked the "dilution" of those cholinergic fibers by its hypertrophic effects on the myometrium. Dilution of the sympathetic myometrial nerve fibers that fail to keep pace with the size of the uterus was also seen in the rat during puberty (Brauer et al 1992) and after acute (Brauer et al 1995) and chronic exposure to estrogen of young adult rats (Chávez-Genaro et al, In press). This unusual behavior of uterine sympathetic nerves clearly contrasts with the responses of similar nerves in other hypertrophic target tissues, including muscular visceral organs, in which changes in target size induce coordinated changes in their innervating neurons (Gabella 1984;Steers et al 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The intercept density of nerve bundles and myometrial nerve fibers was estimated directly under the microscope using a 1-mm-long ocular scale set perpendicular to the uterine long axis and a ϫ 10 objective lens (Brauer et al 1992(Brauer et al ,1995. This orientation of the counting line ensured a comparable sampling because most of the non-vascular nerve fibers in the longitudinal myometrial layer run parallel to the uterine long axis.…”
Section: Nerve Diameter and Nerve Density Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to actual degeneration of sympathetic terminal branches as confirmed using the pan-neuronal marker PGP 9.5 and by electron microscopic analysis (Sporrong et al, 1978;Haase et al, 1997;Brauer and Burnstock, 1998;Zoubina and Smith, 2000). Evidence that these degenerative changes are induced by estrogen comes from findings that acute or chronic administration of estrogen to ovariectomized (OVX) rats or mice results in rapid and robust loss of uterine sympathetic nerve terminals (Brauer et al, 1995; and that mice in which the estrogen receptor ␣ has been rendered nonfunctional show dramatic increases in sympathetic innervation . Circulating estrogen therefore exerts powerful effects on the status of uterine sympathetic innervation.…”
Section: Introductionmentioning
confidence: 96%